The dry grass of August - Mayhew, Anna Jean. (New York : Kensington Books, 2011)
In 1954, 13-year-old Jubie, traveling with her family and her family's black maid Mary Luther--who has always been there for her, making up for her father's rages and her mother's neglect--encounters racial tension and tragedy.
Includes discussion questions.
Keywords: Segregation -- Fiction; Racism -- Fiction